Benin : First Review Under the Three-Year Arrangement Under the Extended Credit Facility, Request for Waiver of Nonobservance of Performance Criterion, Request for Program Extension and Rephasing of Performance Criteria - Staff Report; Press Release; and Statement by the Executive Director for Benin. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Performance under the Extended Credit Facility (ECF) program has been mixed. The revenue slippage was addressed partially with corrective actions. IMF staff supports the authorities' request for a waiver of a missed performance criterion and recommends the completion of the first review. The collapse of a number of unauthorized microfinance institutions has not had a measurable impact on the financial sector. Ex post assessment of performance under the 2005-09 poverty reduction and growth facility program highlighted progress in macroeconomic stabilization but weaknesses in growth performance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet